2020
DOI: 10.1093/geronb/gbaa049
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Employment Histories, Later Health Functioning and National Labor Market Policies: European Findings Based on Life-History Data From SHARE and ELSA

Abstract: Objectives We investigate associations between adverse employment histories over an extended time period and health functioning in later life, and explore whether national labor market policies moderate the association. Methods We use harmonized life history data from the Gateway to Global Aging Data on two European studies (SHARE and ELSA) linked to health beyond age 50 (men= 11,621; women= 10,999). Adverse employment histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
(64 reference statements)
3
10
0
Order By: Relevance
“…Earlier studies identified an association between labour market disadvantages—particular non-standard work, career interruptions and repeated unemployment periods—and negative health outcomes, such as overall poor health and psychological distress (Gal et al 2008 ; Wahrendorf et al 2018 ; van Aerden et al 2016 ; Benach et al 2014 ). Longitudinal findings of recent research identified associations between adverse employment histories and poor health later in life (Wahrendorf et al 2021 ; Hoven et al 2021 ). In addition, employment histories were found to be important predictors of retirement decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies identified an association between labour market disadvantages—particular non-standard work, career interruptions and repeated unemployment periods—and negative health outcomes, such as overall poor health and psychological distress (Gal et al 2008 ; Wahrendorf et al 2018 ; van Aerden et al 2016 ; Benach et al 2014 ). Longitudinal findings of recent research identified associations between adverse employment histories and poor health later in life (Wahrendorf et al 2021 ; Hoven et al 2021 ). In addition, employment histories were found to be important predictors of retirement decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, permanent formality across the working life (measured in this study as social security contributions) appears to be a key positive factor for the mental health of individuals, even when controlling for multiple traditional risk factors. The stability and social protection involved in these working patterns and the consequent access to better financial status, medical care, health services, and housing conditions [ 34 , 35 ] are plausible mechanisms underlying this association with an advantaged mental health status in old age. In contrast, those who experience persistent informality and erratic working patterns, and those who mostly did not work, tend to replicate their accumulated social and financial disadvantages in worse mental health in later life [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, longitudinal studies show that advantaged employment pathways are systematically associated with better mental health in old age, including fewer mental illnesses and depressive symptoms [ 5 , 24 , 30 , 31 , 32 ]. Put in other words, constantly being out of the labor market across adulthood [ 33 ] or permanently working under stressful conditions [ 34 ] or adverse conditions (i.e., involuntary redundancy, weak labor market ties, and disadvantaged occupational status [ 27 , 35 ] lead to poor mental health in late life. According to these authors, the subsequent positive health outcomes among those following advantaged employment pathways are due to persistent adequate labor conditions that allow people to access better financial status, medical care, health services, and housing conditions, as well as to experience lower stress levels and higher community integration across their lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, employment trajectories characterized by standard, continuous, formal, and full-time jobs are associated with an advantaged health status in old age (Madero-Cabib et al, 2019a). After a comprehensive literature review, the only two studies found that have explored the association between adulthood employment paths and subsequent functional limitations provide strong evidence linking adverse employment histories and reduced physical functioning (Wahrendorf et al, 2019(Wahrendorf et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%